PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TALKING STICK TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 5 KOTO XI TARUSAN - Bilkisti, Nisa; Rahmi, Rahmi; Fitri, Dewi Yuliana (Pendidikan Matematika, 2013)
The research was motivated by the studentsâ comprehension of math concept are still low at SMPN 5 Koto XI Tarusan. This research aims to determine the studentsâ comprehension of math concept that apply cooperative learning Talking Stick type better than studentsâ comprehension of math concept that apply conventional learning in class VIII SMPN 5 Koto XI Tarusan. This type of research is experimental research, the design of randomized trials on the subject. The research instrument was a test of understanding mathematical concepts shaped the essay with a reliability test is r11 = 0.904, that is to say about that used reliable. Based on the analysis of the data found that the two classes are normally distributed and homogeneous samples at significance level Î± = 0.05. Hypothesis test results obtained P-value = 0.000 is less than Î± = 0.05, the research hypothesis is accepted. It can be concluded that the students understanding of mathematical concepts using cooperative learning model Talking Stick better than students understanding of mathematical concepts with conventional teaching class VIII SMPN5 Koto XI Tarusan.